Eating behavior, body satisfaction, and self-esteem of selected fourth year high school girls in Iloilo City. - Lee, Mary Rose Virginia L.
This is a descriptive study on the eating behavior, body satisfaction, and self-esteem of 48 fourth year high school girls (15-16 years old ) at Ateneo de Iloilo City., Three survey questionnaires, namely: the Built-R Satisfaction Scale, and Rosenberg's Self-Esteem Scale were utilized in this study. Results indicated that the female high school respondents are normal eaters. They are satisfied with how their bodies look. Their level of self-esteem ranged from moderate to high. The findings are are contrary to Western studies where body satisfaction affects self-esteem.